HLA system. Phenotypic and gene frequencies in celiac and healthy subjects from the same geographical area - Ruiz del Prado, M Y; Olivares López, J L; Lázaro Almarza, A; Lasierra Díaz, M P (Revista española de enfermedades digestivas, 2001)
To compare the phenotypic and gene frequencies of the HLA system in celiac and healthy subjects the same geographical area. HLA A, B, C, DR and DQ phenotypic and gene frequencies have been estimated in 38 celiac children and healthy subjects. The HLA typing has been done according to the microlymphocytotoxicity assay. The individual HLA antigen frequencies in each group have been compared by Chi-square test using Yates correction. For each specificity, the strength of association with celiac disease has been estimated by Odds Ratio and 95% confidence limit. The comparative study of both population show increased phenotypic and gene frequencies among celiac patients and significant differences compared with healthy subjects for B8, Cw7, DR3, DR7 and DQ2. On the contrary, Cw4 and DQ1 phenotypic and gene frequencies are significantly increased in the control population. Our findings support the role of HLA antigens as predisposing factors for celiac disease. The presence of Cw4 and DQ1 can be a protective factor against such disease.